A novel anode structure for diffuse arc anode attachment. (24th June 2021) - Hu, Ya-Hao; Meng, Xian; Huang, He-Ji; Murphy, Anthony B; Shao, Ke; Sun, Su-Rong; Wang, Hai-Xing
Abstract: A novel method for adjusting the direct current arc anode attachment mode by changing the anode surface structure is proposed. A transferred arc device is used to investigate the effect on the arc anode attachment state of the electrode separation and the presence and dimensions of an annular boss, or embossing, on the anode. The experimental results show the diffuse arc anode attachment mode is more likely to be formed in the presence of an annular boss structure on the anode, compared to the standard planar structure. In the case of argon working gas, as the distance between the cathode and the anode increases from 15 mm to 30 mm, the arc maintains the diffuse arc attachment on the anode with the annular boss, while for a planar anode, the arc anode attachment mode changes from diffuse to constricted. Comparison of the measured temperature distribution by the relative intensity method and the emission intensity of the arc attachment region verifies that the annular boss anode can indeed promote diffuse attachment. Analysis of the electric field strength distribution between the electrodes shows that the introduction of the annular boss doubles the electric field strength near the anode surface due to the boss edge effect, which drives the arc to be evenly dispersed on the boss, resulting in the formation of diffuse arc attachment. The enlarged attachment area reduces the current density and heat flux on the anode surface, which is important for the stabilization of diffuse arc attachment. No obvious ablation is found on the surface of the annular boss anode after 1 h operation, while there significant ablation is evident on the surface of the planar anode.